Tracing the Edible and Medicinal Plant Pueraria montana and Its Products in the Marketplace Yields Subspecies Level Distinction Using DNA Barcoding and DNA Metabarcoding - Zhang, Gaixia; Liu, Jinxin; Gao, Mei; Kong, Weijun; Zhao, Qing; Shi, Linchun; Wang, Qiuling (Frontiers in Pharmacology, 2020)
Increased public awareness of nutritional and health issues has resulted in the increasing consumption of food and herbal products made from the root of Pueraria montana var. lobata (kudzu vine) and P. montana var. thomsonii. The famous herbal medicine Yufeng Ningxin, which is used to treat cardiovascular diseases, can be legally produced only using P. montana var. lobata. However, precise identification at the subspecies level is usually challenging when these products’ ingredients lose their morphological characteristics after deep processing. Here, 6 herbarium specimens, 21 expert-identified original plant samples, 30 raw material samples, 10 food products and 12 herbal products were collected to test the subspecies-level authentication abilities of ITS2 sequences. The results showed that ITS2 sequences can distinguish P. montana var. lobata from P. montana var. thomsonii with stable single nucleotide polymorphism (SNP) sites. A total of 93.3% of raw material samples were consistent with the markings on their labels, but only 50% of Gegen Powder samples were made from P. montana var. lobata. High-quality ITS2 sequences were successfully obtained from 9 of the 12 herbal products using Sanger sequencing. Substitution and fungal contamination were detected in 3 herbal products by further DNA metabarcoding, even though thin-layer chromatography (TLC) and high-performance liquid chromatography (HPLC) tests verified that the products met existing quality standards. This study demonstrated that DNA barcoding is a powerful tool for the identification of P. montana var. lobata and P. montana var. thomsonii at the subspecies level, and we conclude that DNA barcodes can be broadly applied to trace the raw materials of food and herbal products.